EVALUATION OF ENZYMATIC ACTIVITY OF Pleurotus ostreatus REGARDING STAGES OF MYCELIUM DEVELOPMENT - Aneta Sławińska; Janusz Kalbarczyk (Acta Scientiarum Polonorum: Hortorum Cultus, 2011)
The aim of the study was to evaluate cellulolytic and amylolytic enzymes activities in substrates, regarding the time of the Pleurotus ostreatus (Mori Hiratake no 39) B7 mycelium incubation, and the stage of physiological development. The experiment was divided into three parts which had different times of mycelium incubation before fructification: I – the time of incubation – 2 weeks; II – 4 weeks; III – 6 weeks. After the mycelium incubation, cold-shock and mechanical-shock was provided on each series. Researches proved that agents such as the time of mycelium incubation in substrate, agrotechnical treatment (cold-shock, mechanical-shock), and the type of mycelium layer had an impact on cellulolytic and amylolytic activity of mycelium in the cultivation’s substrate. The biggest influence on change of enzymatic activity had agrotechnical treatment: cold-shock and mechanical-shock.